Question (i)
"\\left(D^2-2DD'+[D']^2\\right)z=\\tan(x-y)\\longrightarrow\\\\[0.3cm]\nz=C.F.+P.I."
1 STEP: We try to find C.F.
"\\left(D^2-2DD'+[D']^2\\right)z=0"
The auxillary equation is
"m^2-2m+1=0\\longrightarrow\\\\[0.3cm]\nm_{1,2}=1"
Then,
"C.F.=f_1(y+1\\cdot x)+x\\cdot f_2(y+1\\cdot x)\\\\[0.3cm]\n\\boxed{C.F.=f_1(y+x)+x\\cdot f_2(y+x)}"
2 STEP: We try to find P.I.
Let us give some theory to understand how to solve this equation:
If "F(x,y)" is any function, resolve "F(D,D')" into linear factors say
"(D-m_1D'),(D-m_2D'),\\ldots,(D-m_nD')"
then,
"P.I.=\\displaystyle\\frac{1}{(D-m_1D')\\cdot\\ldots(D-m_nD')}F(x,y)"
Note:
"(1)\\,\\,\\frac{1}{(D-mD')}F(x,y)=\\int F(x,c-mx)dx,\\,\\,\\text{where}\\,\\,y=c-mx\\\\[0.3cm]\n(1)\\,\\,\\frac{1}{(D+mD')}F(x,y)=\\int F(x,c+mx)dx,\\,\\,\\text{where}\\,\\,y=c+mx\\\\[0.3cm]"
In our case,
"P.I.=\\frac{1}{(D-1\\cdot D')(D-1\\cdot D')}\\tan(x-y)=\\\\[0.3cm]\n=\\frac{1}{(D-1\\cdot D')}\\int\\tan(x-(c-1x))dx=[1x+y=c]=\\\\[0.3cm]\n=\\frac{1}{(D-1\\cdot D')}\\int\\tan(2x-c)dx=\\\\[0.3cm]\n=\\frac{1}{(D-1\\cdot D')}\\left(\\frac{-1}{2}\\cdot\\ln|\\cos(2x-c)|\\right)=\\\\[0.3cm]\n=\\int\\left(\\frac{-1}{2}\\cdot\\ln|\\cos(2x-c)|\\right)dx"
(More information about "\\int\\tan(x)dx": https://en.wikipedia.org/wiki/List_of_integrals_of_trigonometric_functions)
Conclusion,
"\\boxed{P.I.=-\\frac{1}{2}\\cdot\\int\\ln|\\cos(2x-c)|dx}"
General conclusion,
"z=C.F.+P.I.\\longrightarrow\\\\[0.3cm]\n\\boxed{z=f_1(y+x)+x\\cdot f_2(y+x)-\\frac{1}{2}\\cdot\\int\\ln|\\cos(2x-c)|dx}"
Question (ii)
"z(p-q)=z^2+(x+y)^2\\longrightarrow\\\\[0.3cm]\nzp+(-z)q=(z^2+(x+y)^2)"
The auxillary equation is
"\\frac{dx}{z}=\\frac{dy}{-z}=\\frac{dz}{z^2+(x+y)^2}\\\\[0.3cm]"Then,
"\\frac{dx}{z}=\\frac{dy}{-z}\\longrightarrow\\frac{dx}{1}=\\frac{dy}{-1}\\longrightarrow\\\\[0.3cm]\ndx+dy=0\\longrightarrow d(x+y)=0\\longrightarrow\\\\[0.3cm]\n\\boxed{x+y=C_1}\\\\[0.3cm]\n\\frac{dx}{z}=\\frac{dz}{z^2+(x+y)^2}\\longrightarrow dx=\\frac{zdz}{z^2+C_1^2}\\longrightarrow\\\\[0.3cm]\nx=\\frac{1}{2}\\cdot\\int\\frac{d(z^2)}{z^2+C_1^2}\\longrightarrow x=\\frac{1}{2}\\cdot\\ln|z^2+C_1^2|-\\frac{1}{2}\\ln|C_2|\\longrightarrow\\\\[0.3cm]\n2x=\\ln\\left|\\frac{z^2+C_1^2}{C_2}\\right|\\longrightarrow e^{2x}=\\frac{z^2+C_1^2}{C_2}\\\\[0.3cm]\n\\boxed{C_2=\\frac{z^2+C_1^2}{e^{2x}}}\\\\[0.3cm]" Conclusion,
"\\boxed{\\text{Solution of equation is}\\,\\,\\varphi\\left((x+y),e^{-2x}(z^2+(x+y)^2)\\right)=0}"
ANSWER
Question (i)
"z=f_1(y+x)+x\\cdot f_2(y+x)-\\frac{1}{2}\\cdot\\int\\ln|\\cos(2x-c)|dx"
Question (ii)
"\\varphi\\left((x+y),e^{-2x}(z^2+(x+y)^2)\\right)=0"
Comments
Leave a comment